PENGGUNAAN VECM DALAM MEMPREDIKSI NILAI AKTIVA BERSIH REKSA DANA SYARIAH MELALUI INDEKS HARGA SAHAM GABUNGAN DAN INFLASI - Sitti Mua'limah; M. Qoshid Al Hadi; Iman Setya Budi (BIMA: Jurnal Bisnis dan Manajemen, 2023)
Capital markets play an important role in the modern economy, and a deep understanding of the factors that influence the value of investment assets is key for investors and financial practitioners. In the context of the Indonesian capital market, the Composite Stock Price Index (IHSG) and the inflation rate are two macroeconomic variables that are very relevant in investment performance analysis. This research aims to investigate the influence of the IHSG and inflation on the Net Asset Value (NAV) of mutual funds, with a focus on short-term and long-term aspects. This research adopts a quantitative method with a descriptive approach. Monthly data on IHSG, inflation and NAV of mutual funds for the period January 2011 to December 2021 are used for analysis. The Vector Error Correction Model (VECM) is used to test the short-term and long-term influence of IHSG and inflation on mutual fund NAV. This research has originality because it focuses on analyzing the influence of IHSG and inflation on mutual fund NAV in the context of Islamic Hajj mutual funds in Indonesia with VECM. The results of this research can also provide practical guidance for investors and mutual fund managers in making investment decisions. The findings from this study show that, in the longer term, IHSG has a significant impact on the NAV of Sharia Hajj Mutual Fund products at PT. Insight Investment Management, while inflation does not have a significant impact on NAV.